Considerations for improving quality of care of patients with rheumatoid arthritis and associated comorbidities. Issue 2 (18th July 2020) - Kvien, Tore K; Balsa, Alejandro; Betteridge, Neil; Buch, Maya H; Durez, Patrick; Favalli, Ennio Giulio; Favier, Guillaume; Gabay, Cem; Geenen, Rinie; Gouni-Berthold, Ioanna; van den Hoogen, Frank; Kent, Alison; et al.
Abstract : Objective: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disorder with a global prevalence of approximately 0.5–1%. Patients with RA are at an increased risk of developing comorbidities (eg, cardiovascular disease, pulmonary disease, diabetes and depression). Despite this, there are limited recommendations for the management and implementation of associated comorbidities. This study aimed to identify good practice interventions in the care of RA and associated comorbidities. Methods: A combination of primary research (180+ interviews with specialists across 12 European rheumatology centres) and secondary research (literature review of existing publications and guidelines/recommendations) were used to identify challenges in management and corresponding good practice interventions. Findings were prioritised and reviewed by a group of 18 rheumatology experts including rheumatologists, comorbidity experts, a patient representative and a highly specialised nurse. Results: Challenges throughout the patient pathway (including delays in diagnosis and referral, shortage of rheumatologists, limited awareness of primary care professionals) and 18 good practice interventions were identified in the study. The expert group segmented and prioritised interventions according to three distinct stages of the disease: (1) suspected RA, (2) recent diagnosis of RA and (3) established RA. Examples of good practice interventions included enabling self-management (self-monitoring and disease management support, for example, lifestyle adaptations); early arthritis clinic; rapid access to care (online referral, triage, ultrasound-guided diagnosis); dedicated comorbidity specialists; enhanced communication with primary care (hotline, education sessions); and integrating patient registries into daily clinical practice. Conclusion: Learning from implementation of good practice interventions in centres across Europe provides an opportunity to more widely improved care for patients with RA and associated comorbidities.